1994
DOI: 10.1210/endo.134.2.7507840
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression patterns of insulin-like growth factor binding proteins 2 and 5 during fetal and postnatal development.

Abstract: Insulin-like growth factors (IGFs), when isolated from serum or tissue fluids, are usually found as part of a protein complex which also contains one of several IGF binding proteins (IGFBPs). Although some IGFBPs have been shown to alter interactions of IGFs with their receptors in vitro and can modify the responses of cultured cells to exogenous IGFs, the in vivo functions of IGFBPs remain unclear. This study examines expression of a recently described IGFBP gene, IGFBP-5, in the rat embryo and fetus and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 1 publication
4
43
0
Order By: Relevance
“…It belongs to a family of secreted proteins that bind IGF1 and 2, thereby modulating their biological actions. It is known to be expressed in embryogenesis during muscle development (32) and is rapidly induced during terminal muscle differentiation of C2l myoblasts coincident with the onset of Myogenin gene expression (33). Indeed, we found that PF-1, the clone that expressed the highest level of Myogenin, also showed high levels of Igfbp5.…”
Section: Induction Of a Myogenic Transcription Program By Pax3-fkhrmentioning
confidence: 58%
“…It belongs to a family of secreted proteins that bind IGF1 and 2, thereby modulating their biological actions. It is known to be expressed in embryogenesis during muscle development (32) and is rapidly induced during terminal muscle differentiation of C2l myoblasts coincident with the onset of Myogenin gene expression (33). Indeed, we found that PF-1, the clone that expressed the highest level of Myogenin, also showed high levels of Igfbp5.…”
Section: Induction Of a Myogenic Transcription Program By Pax3-fkhrmentioning
confidence: 58%
“…IGF-I can stimulate the proliferation of dissociated limb mesenchymal cells (Kaplowitz et al, 1982) and explanted limb buds Bhaumick and Bala, 1987), suggesting that IGF-I might be involved in promoting the proliferation and outgrowth of limb mesoderm in response to the AER. In addition, IGF peptides and IGF-I receptors are present in the AER itself (Ralphs et al, 1990;, and IGF binding protein-2 (IGFBP-2) and IGF binding protein-5 (IGFBP-5), which can modulate the activity of IGF-I, are expressed by the AER of the rat limb bud (Streck et al, 1992;Green et al, 1994), suggesting the possibility that IGF-I may be involved in some aspect of AER activity. Insulin is also present in the chick and mouse embryo during early stages of limb development (De Pablo et al, 1982;Spaventi et al, 1990;Deltour et al, 19931, and specific insulin receptors are present in the chick limb bud during its outgrowth (Bassas et al, 1988), although their spatial distribution has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, Igfbp5 is expressed in the embryo from early development, principally in the myotomal component of the somites and developing central nervous system (8). Postnatally, serum IGFBP-5, in common with IGFBP-3, forms a ternary complex with IGF-I or IGF-II and the acid-labile subunit (9).…”
mentioning
confidence: 99%